2022
DOI: 10.1038/s41467-022-30420-6
|View full text |Cite
|
Sign up to set email alerts
|

Chiral emergence in multistep hierarchical assembly of achiral conjugated polymers

Abstract: Intimately connected to the rule of life, chirality remains a long-time fascination in biology, chemistry, physics and materials science. Chiral structures, e.g., nucleic acid and cholesteric phase developed from chiral molecules are common in nature and synthetic soft materials. While it was recently discovered that achiral but bent-core mesogens can also form chiral helices, the assembly of chiral microstructures from achiral polymers has rarely been explored. Here, we reveal chiral emergence from achiral co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 68 publications
1
55
0
Order By: Relevance
“…Our recent work has demonstrated that, when dissolved in a mutual solvent such as chloroform and chlorobenzene, PII‐2T polymer chains/fiber aggregates adopt chiral helical structure shown in Figure 2 and Figure S10 (Supporting Information). [ 33 ] Unlike the amorphous ones in CN, the semicrystalline aggregates in DCB give a vibronic progression in the UV–vis low‐energy absorption band, which we attribute to aggregation‐induced backbone planarization (Figure 1c). The vibronic progression in DCB, however, exhibits a lower A 0–0 / A 0–1 ratio than that in decane, possibly owing to a relatively tortional/helical chain conformation in the aggregates.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Our recent work has demonstrated that, when dissolved in a mutual solvent such as chloroform and chlorobenzene, PII‐2T polymer chains/fiber aggregates adopt chiral helical structure shown in Figure 2 and Figure S10 (Supporting Information). [ 33 ] Unlike the amorphous ones in CN, the semicrystalline aggregates in DCB give a vibronic progression in the UV–vis low‐energy absorption band, which we attribute to aggregation‐induced backbone planarization (Figure 1c). The vibronic progression in DCB, however, exhibits a lower A 0–0 / A 0–1 ratio than that in decane, possibly owing to a relatively tortional/helical chain conformation in the aggregates.…”
Section: Resultsmentioning
confidence: 87%
“…As shown in Figure S12 (Supporting Information), the 0–0 and 0–1 peak locations blueshift, and their absorption peak ratio 0–0/0–1 decreases with concentration, indicating a decrease in the J ‐coupling character and possibly an increase in backbone torsion from isotropic to various mesophases. [ 33 ] These mesophases discovered in DCB solutions are comprised of aligned polymer fiber aggregates instead of single polymers according to SEM shown in Figure 3b. Therefore, we deduce that balanced backbone and side‐chain interactions conferred by mutual solvents are important for forming such liquid crystals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations